2017
DOI: 10.1111/anae.14039
|View full text |Cite
|
Sign up to set email alerts
|

The association of postoperative pulmonary complications in 109,360 patients with pressure‐controlled or volume‐controlled ventilation

Abstract: We thought that the rate of postoperative pulmonary complications might be higher after pressure-controlled ventilation than after volume-controlled ventilation. We analysed peri-operative data recorded for 109,360 adults, whose lungs were mechanically ventilated during surgery at three hospitals in Massachusetts, USA. We used multivariable regression and propensity score matching. Postoperative pulmonary complications were more common after pressure-controlled ventilation, odds ratio (95%CI) 1.29 (1.21-1.37),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 43 publications
(57 reference statements)
1
40
1
2
Order By: Relevance
“…A recent randomized controlled trial during lumbar spine surgery demonstrated that hemodynamic variables and arterial blood gas results did not differ significantly between the VCV and PCV with volume guaranteed (PCV-VG) mode groups [13]. Also, a recent large observational study suggested that PCV is associated with increase of PPC compared to VCV [22]. This association is not confirmed by our results.…”
Section: Ventilator Strategies In Patients Undergoing Neurosurgical Icontrasting
confidence: 91%
“…A recent randomized controlled trial during lumbar spine surgery demonstrated that hemodynamic variables and arterial blood gas results did not differ significantly between the VCV and PCV with volume guaranteed (PCV-VG) mode groups [13]. Also, a recent large observational study suggested that PCV is associated with increase of PPC compared to VCV [22]. This association is not confirmed by our results.…”
Section: Ventilator Strategies In Patients Undergoing Neurosurgical Icontrasting
confidence: 91%
“…Small RCTs in laparoscopic bariatric surgery have yielded similar results 109110. No data from prospective trials are available to evaluate whether these benefits translate to improved clinical outcomes; however, a large database study involving more than 100 000 patients having elective surgery reported that use of PCV was associated with increased odds of developing a PPC (odds ratio 1.29, 1.21 to 1.37; P<0.001) 111. In this study, use of PCV predisposed to higher tidal volumes and driving pressures, a possible mechanism for the findings.…”
Section: Additional Considerationsmentioning
confidence: 99%
“…We thank Dr. McGuckin for his interest in our article [1] and appreciate the opportunity to respond to his queries. Dr. McGuckin raises the question of the applicability of our findings to patients' lungs being ventilated via supraglottic airways.…”
Section: Mechanical Ventilation Mode and Postoperative Pulmonary Compmentioning
confidence: 99%